KETIDAKPASTIAN LINGKUNGAN DAN MANAJEMEN LABA DENGAN KEMAMPUAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Iswajuni; Bryan Luke (Universitas Airlangga, 2023)
This study aims to examine the effect of environmental uncertainty on earnings management, with managerial ability as moderation. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017 - 2021. The sampling technique used purposive sampling, resulting in 344 annual reports of manufacturing companies. The data analysis technique uses moderated regression analysis (MRA). The results showed that environmental uncertainty had a positive effect on earnings management and indicated that managerial ability weakened the effect of environmental uncertainty on earnings management. The theoretical contribution of this research is to strengthen contingency theory in describing earnings management practices that occur due to environmental uncertainty, and can be weakened when supported by adequate managerial ability. Contributions for investors, can be used as a strategy in managing investment portfolios by considering internal factors such as managerial capabilities that can reduce earnings management practices, and external factors such as environmental uncertainty that can increase earnings management practices.